Pembuatan Website Catalog Pariwisata Kabupaten Toraja Utara - Saputra, Fredy Dwiarditya; Setiabudi, Djoni Haryadi; Palit, Henry Novianus (Jurnal Infra, 2016)
North Toraja Regency is one of the regencies in Indonesia which is actively developing itself as a tourist destination. North Torajaâs tourism has its own uniqueness. It offers different types of tourist attractions compared to those of other regencies. However, due to the lack of tourism information, both local and foreign tourists have not considered North Toraja as an attractive tourist destination. Based on the problem described, there is a need to make a catalogue website that aims to give clear and accurate information regarding North Torajaâs various tourist spots.Important information such as North Torajaâs rich history, tourist spots, public facilities, arts and crafts, and annual traditional activities or events are all provided in this catalogue website. Thus, tourists can easily obtain complete information about North Torajaâs tourism. This website was created using programming languages like PHP, JavaScript, and MySQL database.The catalogue website has many features and information such as user profile, map, tourist spots, public facilities, culture, arts, traditional food, events, recommendations, and photo gallery.